BUILDING A LINUX-BASED VPN SERVER USING POINT TO POINT TUNNELING PROTOCOL (PPTP) - Aqilla Fadia Haya; Hafizh Al Karim; Muhammad Rizky Perdana; Ahmad Nur Ihsan Purwanto; Mutiara Persada Pulungane (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2021)
Virtual Private Network (VPN) technology has an important role in today's world of communication, VPNs are able to create local networks using facilities. Because a corporate VPN can make connecting information easy and secure. But nowadays, VPNs are gaining popularity for personal use due to the increasing number of interactions that require users to surf the web. On a VPN system that uses the Point to Point Tunneling Tradition (PPTP) method that we created, we use a server from Linux that will connect to Windows as a user. So that clients or windows can connect to the web using a VPN server from linux.